Тернарна логіка в майбутньому - Назаренко, Ю. В. (ХНУРЕ, 2020)
This article is devoted to some problems of modern logic. Elements and basic principles of mathematical logic are the basis of logical elements and logical devices of electronic computers, are the basis of algorithms and programming languages, logical programming systems, databases and expert systems. However, the binary principle, established in mathematical logic, does not correspond to the tasks of modern programming. Therefore, in recent decades, the so-called three-valued logic has been actively developed.
Keywords: філософія; тернарна логіка